Prevalence Based Etiological Estimation Of Locations Of Fracture Of Conventional Complete Dentures Made With Balanced Occlusion Philosophy: An Original Research Study (Journal of Pharmaceutical Negative Results, 2023)
Background & Aim: Acrylic fracture is one of the commonest problems seen in conventional complete dentures. This fracture can be due to various reasons and at different locations. Therefore, this study was primarily conducted to estimate the prevalence and etiologies of location related fractures of complete dentures made with balanced occlusion philosophy.Materials and Methods: Total 50 patients with the chief compliant of their broken complete dentures, were included logically. Dentures made only with balanced occlusion philosophy were included in the study. Systematic sampling procedure was utilized rationally to select all participating subjects. Total 30 male and 20 female patients were studied in comprehensively. Each denture was examined carefully for the details of fracture. The dentures were repaired as per the requirements and standards. The probable etiology of the denture fracture was asked from the patients. All data was sent for statistical analysis for further analysis and interpretations. P value less than 0.05 was taken as significant.Statistical Analysis & Results: All data was statistically analyzed by SPSS statistical package for the Social Sciences version 21 for Windows. In the first age range of 45-50 years, total 17 patients were noticed. P value was highly significant for this group (0.01). Fracture (Midline) was noticed in maximum 19 patients whereas Fracture (with teeth) was noticed in only 2 patients. P value was highly significant in the Fractures noticed at midline areas (0.01). Denture fracture due to Poor fit was identified in 12 patients. P value was highly significant here (0.02). For ill fit group, the measured Statistical Mean was 0.738, standard error was 0.403, 95% coefficient I was 1.96, Pearson Chi-Square Value was 1.838 and Level of Significance (p value) was 0.02.Conclusion: It was concluded that midline fracture was the most common site of fracture followed by canine region and premolar/molar region. Likewise, the most common etiology of denture fracture was accidental fall followed by loose fit and faulty occlusion. However, authors also expect other long term studies with larger sample size and wider parameters so as to set other related recommendations.